Constructing and applying a thinking patterns test to students of the Art Education Department (Al-Academy, 2025)
Thinking constitutes a mental process in which the visual sensory perception of the person (the learner) interacts with what he has acquired from educational experiences throughout the stages of development and the level of his intelligence that he possesses to achieve a specific goal based on the motivation that moves his energies to remove the obstacles or problems that he faces in life and social situations, based on From the above, the current research stops at a basic variable represented by patterns of thinking. Therefore, the research problem was crystallized according to the following question in proportion to the problem of their research: What is the pattern of thinking among students of the College of Fine Arts?Since the current research aims to (reveal the level of visual culture and its relationship to the thinking patterns of students at the College of Fine Arts), the researchers have therefore adopted the descriptive approach as it is the most appropriate scientific method to achieve the goal of the research.As the research population consisted of third-year students in the scientific departments (art education - plastic arts - design) affiliated with the College of Fine Arts, morning study for the academic year 2022-2023, numbering (335 male and female students), the sample of the current research was represented by (80) male and female students. Since the research contains a basic variable represented by (thinking patterns), the two researchers built a type of test, which is the thinking patterns test.In this research, the two researchers used the Statistical Package for the Social Sciences - SPSS to extract the results and conclusions, the most important of which are:The emergence of three patterns of thinking that characterize third grade students (in general) in the scientific departments (art education - fine arts - design) affiliated with the College of Fine Arts, represented by the contemplative, visual, and creative style.